2019
DOI: 10.2147/idr.s219358
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antibiotic susceptibility profile and prevalence of <em>mecA</em> and <em>lukS-PV/lukF-PV</em> genes in <em>Staphylococcus aureus</em> isolated from nasal and pharyngeal sources of medical students in Ecuador</p>

Abstract: Background Staphylococcus aureus is a common nasal colonizer in 20–30% of the general population. When mucosal and cutaneous barriers are disrupted, S. aureus can cause severe infections. While MRSA nasal carriers have an increased risk of infections when compared to non-carriers, prolonged exposure to the hospital environment may cause an increase in carriage of MRSA. Materials and methods A survey questionnaire was filled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(45 reference statements)
3
16
2
Order By: Relevance
“…This finding is in line with previous researchers in Brazil and Ethiopia, who reported 5.1% and 5.8% of MRSA colonization respectively. 18 , 23 In Ecuador, the prevalence of MRSA, detected in this study, was higher than a previous study carried out in Quito 10 that reported a prevalence of 2.4% but lower than the study into medical students 19 that reported a 7.1% prevalence of MRSA. A similar prevalence was demonstrated in other Latin American countries, such as Argentina, where a study in hospitals showed that the overall MRSA acquisition rate was 2.3/1000 patient-days-at-risk with a MRSA acquisition prevalence of 1.96% 24 Of course, there are studies that have shown a much higher MRSA colonization prevalence.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This finding is in line with previous researchers in Brazil and Ethiopia, who reported 5.1% and 5.8% of MRSA colonization respectively. 18 , 23 In Ecuador, the prevalence of MRSA, detected in this study, was higher than a previous study carried out in Quito 10 that reported a prevalence of 2.4% but lower than the study into medical students 19 that reported a 7.1% prevalence of MRSA. A similar prevalence was demonstrated in other Latin American countries, such as Argentina, where a study in hospitals showed that the overall MRSA acquisition rate was 2.3/1000 patient-days-at-risk with a MRSA acquisition prevalence of 1.96% 24 Of course, there are studies that have shown a much higher MRSA colonization prevalence.…”
Section: Discussioncontrasting
confidence: 79%
“… 18 Another study in Quito in 2019 reported an even higher colonization rate of 57.8% (186/322) among medical students. 19 However, it should be mentioned that the 2019 study in Quito involved nasal and throat swabs, whereas our study only analyzed nasal swabs. Some studies have shown that pharyngeal colonization can be higher than nasal colonization.…”
Section: Discussionmentioning
confidence: 83%
“…Of more interest, the PVL-encoding genes detected in this work were all from non-severe cases, and no blood, tissue or ETA specimens had isolates that were PVL-positive. Association of PVL with non-severe cases has been recognized [ 31 , 32 ], but the reverse was also sporadically reported [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with other studies concluded that pvl prevalence among S. aureus isolates varies between geographical areas or the type of patients (e.g., children vs. adults) [ 33 ], from 3% to 75% [ 34 , 35 , 36 ]. Interestingly, the majority of pvl -positive strains in our study were MRSA, an observation that aligns with earlier reports [ 33 , 37 , 38 , 39 ]. For example, a study performed in Alaska in 2000 reported that while no MSSA isolates carried the pvl genes, 92% of MRSA isolates had the toxin [ 39 ].…”
Section: Discussionmentioning
confidence: 99%